Analysis of Consumers Rational and Emotional Motives in Making Purchases to Improve Marketing Strategy - Aldrian Wibowo; Cecep Safa'atul Barkah; Arianis Chan; Pratami Wulan Tresna (Indonesian Business Review, 2023)
This research was conducted to analyze the rational and emotional motivation of consumers to make purchases/visit Colada Cafe. Those consumer motivations are rational buying motives and emotional buying motives. The results of this study will be used as a basis for making decisions to improve the marketing strategy carried out by Colada Cafe so that it can compete with competitors. This research was conducted using quantitative research methods with descriptive analysis techniques. Samples from this method were taken using simple random sampling. The sample in this study was 90 Colada Cafe consumers. Based on the data obtained, it can be concluded that the marketing strategy Colada Cafe should do is expanding parking lots, improving promotional methods that not only show the interior but also show prices, promos, taste testimonials, menu variations, good service, strategic locations, and appetizing product displays. In addition, Colada Cafe must improve the quality of the products served to consumers.